The diplomat-scholar a biography of Leon Ma. Guerrero - Fernandez, Erwin Soriano (ISEAS-Yusof Ishak Institute, 2017)
Leon Ma. Guerrero (1915-82), a top-notch writer and diplomat, served six Philippine presidents, beginning with President Manuel L. Quezon and ending with President Ferdinand E. Marcos. In this first full-length biography, Guerrero's varied career as writer and diplomat is highlighted from an amateur student editor and associate editor of a prestigious magazine to ambassador to different countries that reflected then the exciting directions of Philippine foreign policy. But did you know that he served as public prosecutor in the notorious Nalundasan murder case, involving the future Philippine president? Did you also know that during his stint as ambassador to the Court of Saint James he wrote his prize-winning biography of Philippine national hero, Jose Rizal? Learn more about him in this fully documented biography recounting with much detail from his correspondence the genesis and evolution of his thinking about the First Filipino, which is the apposite title of his magnum opus